Fuzzy formalization of the multi-stage processes temporal description - Lomazov, A V; Lomazov, V A; Rumbesht, V V (Journal of physics. Conference series, 2020)
The problem of constructing the periodization of socio-economic and organizational-technological processes, which makes it possible to divide them into stages for a more detailed study, is considered. The methodological basis of the study is the conceptual apparatus of L. Zadeh's theory of the linguistic variable in combination with expert assessment technologies. According to the specifics of the description of non-stationary processes, a linguistic variable has been developed, the values of which (temporal terms) correspond to the stages of the process. A new type of temporal terms that are semantically described by bitrapezoidal membership functions is proposed, and an expert procedure for constructing these terms is indicated. A system of algebraic operations on temporal terms is proposed and justified (by statements on properties), which allows formulating syntactic and semantic rules for the transformation of terms. The proposed formal linguistic description of the stages allows the analysis of socio-economic and organizational-technological processes using the procedure of fuzzy inference based on a fuzzy production rule about the subject area, which can help increase the scientific validity of management decisions.